Herpes simplex virus type 1 related acute retinal necrosis following an encephalitis illness: a case report - Zhong, Pingting (BMC Neurol, 2021)
BACKGROUND: Virus encephalitis is found to be a risk factor for acute retinal necrosis (ARN). CASE PRESENTATION: We herein presented a case of a 20-year-old teenage boy who suffered from encephalitis of unknown etiology with early negative pathologic results, and was primarily treated with systemic administration of high-dose steroids without antiviral therapy. He later had sudden vision loss in his right eye. Intravitreal and intravenous antiviral treatments were immediately started due to suspected ARN. Herpes simplex virus (HSV)-1 was identified later in the vitreous humor of the patient. After the surgery of retinal detachment (RD), obvious improvements in vision were observed. However, the patient had recurrent RD and vision declination 5 weeks later. CONCLUSIONS: The case with suspected viral encephalitis should be treated with antiviral therapy regardless of early virologic results in order to avoid complications of a missed viral encephalitis diagnosis, especially if systemic steroid treatment is being considered.